Does insecure attachment lead to (mis)wired brains? Emotion, cognition, and attachment: an outlook through psychophysiological pathways - Silva, Catarina Gonzalez da (2013)
The evolutionary-based attachment theory (Bowlby, 1969, 1973, 1980) asserts that approach/attachment or avoidance/withdrawal tendencies may reflect distinct regulation strategies underlying individual differences in attachment styles. The influence of the internal working models of attachment on emotion and cognition, and more recently, on its psychophysiological underpinnings has been a central focus of research. Despite the endeavours at clarifying this modulatory influence in behaviour, inconsistent results have prevented definite answers. Aiming at contributing to the current knowledge in the filed, and embedded in a psychophysiological framework, the present thesis brings together findings of empirical studies focusing on the regulation abilities in attentional bias towards emotion information. Following an integrative approach, these studies coupled behavioural responses with measures of skin conductance, heart rate, and eye movements. Findings of these studies converge to show distinctive features between regulation strategies deployed by insecure attached individuals when processing threat-related information on visual attention tasks, as measured by behavioural (Study I), sympathetic (Study II), and eye movement (Study III) responses. Taken together these findings point up the evolutionary value of the attachment behavioural system, providing support for fundamental distinctions between insecure attachment styles, both at a behavioural and physiological level. Considering recent advances emerging in the filed, results are discussed within in a comprehensive and all-encompassing approach.